2014
DOI: 10.1093/inthealth/ihu024
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing acute and prevalent HIV-1 infection in young African adults seeking care for fever: a systematic review and audit of current practice

Abstract: Fever is a common complaint in HIV-1 infected adults and may be a presenting sign of acute HIV-1 infection (AHI). We investigated the extent to which HIV-1 infection was considered in the diagnostic evaluation of febrile adults in sub-Saharan Africa (SSA) through a systematic review of published literature and guidelines in the period 2003–2014. We also performed a detailed audit of current practice for the evaluation of febrile young adults in coastal Kenya. Our review identified 43 studies investigating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…These studies demonstrate that far from being a rare event, AHI is likely a common clinical syndrome in HIV endemic parts of sub-Saharan Africa. These results have yet to translate into clinical practice or guidance recommending widespread AHI testing in general medical settings in sub-Saharan Africa [30•,31•]. However, this may change with improved, cheaper AHI diagnostics that are now becoming available.…”
Section: Clinical Markers Of Acute Hiv Infectionmentioning
confidence: 99%
“…These studies demonstrate that far from being a rare event, AHI is likely a common clinical syndrome in HIV endemic parts of sub-Saharan Africa. These results have yet to translate into clinical practice or guidance recommending widespread AHI testing in general medical settings in sub-Saharan Africa [30•,31•]. However, this may change with improved, cheaper AHI diagnostics that are now becoming available.…”
Section: Clinical Markers Of Acute Hiv Infectionmentioning
confidence: 99%
“…In a systematic review of adults seeking outpatient care from clinics in sSA in the period 2003–2014, 34 (79%) of 43 studies identified focused on malaria only. The remaining studies investigated the following aetiologies: acute HIV-1 infection (AHI) and malaria (2 studies), human herpes virus-8 and hepatitis B virus (1 study), pneumococcal bacteraemia (1 study), flaviviruses (1 study), influenza viruses (1 study), Lassa virus (1 study), intestinal helminths (1 study) and schistosomiasis (1 study) [4]. …”
Section: Introductionmentioning
confidence: 99%
“…This was also shown in a study in Singapore, where, among patients >15 years old suspected of dengue by emergency physicians, 8/294 (2.4%) acute phase HIV patients were identified; of these, 7 satisfied World Health Organization (WHO) case classification criteria for probable dengue 11 . Strategies to identify acute HIV infection have been proposed 12 and should be used concurrently to improve the incorporation of these patients into care.…”
Section: Patients With Incident Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%